POPULATION DEVELOPMENT IN INDONESIA - Wily Julitawaty (UNIVERSITAS PEMBANGUNAN PANCA BUDI, 2019)
The population is influenced by birth (fertility), death (mortality) and population migration. The process of changing dynamic elements is called a dynamic process in the population structure. The reasons for this change must be studied in their changes and developments. The purpose of this study was to determine the level of labor force participation in Indonesia. This study uses a time series secondary data published by the Central Bureau of Statistics, namely the labor force participation rate according to the Province from 2010 to 2015. Hope to enjoy a demographic bonus if it reaches 70 percent of the Labor Force Participation Rate.